Supply Chain Risk Mapping at ABC Cement Plant in Aceh, Indonesia - Lufika*, Raihan Dara; Sastra, Hasan Yudie; Sentia, Prima Denny; Ilyas, Ilyas; Iskandar, Iskandar (Graduate School of Universitas Syiah Kuala, 2022)
Supply Chain Risk Management is an industry collaboration that works with partners in the supply chain system to implement a risk management process in dealing with the emergence of risks and uncertainties caused by logistics activities or other resources in the supply chain. Every industry deals with risk. This study aims to identify, classify, and map supply chain activities and their risks. In the initial stage, supply chain events are identified through interviews and brainstorming. Then, these events are portrayed in the supply chain map. Then, the risk identification stage used a rating scale to determine the level of likelihood and consequence based on three SCOR elements. There are 40 risk events in this study which are 13 risk events in the source section, 19 risk events in the make section, and eight risk events in the delivery section. Finally, it is necessary to calculate the value of the Risk Priority Index. The Risk Priority Index is the basis of the risk mapping stage. The risk map shows the urgency to treat each risk event.